The Laws of Ine. Report of a Digital Edition of a Renaissance Manuscript - Fabio Soncin (Umanistica Digitale)
This report describes the implementation of a digital edition of the Laws of Ine as part of my MA final dissertation, contained in MS Additional 43703, transcribed in 1562 by the English antiquarian Laurence Nowell. The Laws of Ine are an important juridical text for the Anglo-Saxon period and in the context of Tudor England for the creation of British identity. The objective is to demonstrate the usefulness of the digital medium for the valorization of the historical dimension of the manuscript and the text. The edition has been implement using the visualization software EVT 1.3, whose advantages and disadvantages will be taken into consideration. Even if EVT 1.3 is outdated compared to its latest version (EVT 2), this software is versatile enough for the creation of digital editions with a low degree of complexity.